Immune-enhancing effects of glucocorticoids in response to day–night cycles and stress. (25th July 2020) - Shimba, Akihiro; Ikuta, Koichi
Abstract: Environmental cues such as the day–night cycle or stressors trigger the production of glucocorticoids (GCs) by the adrenal cortex. GCs are well known for their anti-inflammatory effects that suppress the production of inflammatory cytokines and induce the apoptosis of lymphocytes. Recent studies in mice, however, have revealed pro-inflammatory effects. The diurnal oscillation of GCs induces the expression of IL-7 receptor α (IL-7Rα) and C–X–C motif chemokine receptor 4 (CXCR4) at the active phase, which drives the diurnal homing of T cells into lymphoid organs. This accumulation of T cells at the active phase enhances T-cell priming against bacterial infection and antigen immunization, leading to an increase of effector CD8 T cells and antibody production. GCs induced by moderate stress trigger the homing of memory CD8 T cells into the bone marrow and support the maintenance and response of these cells. Thus, endogenous GCs have a self-defense function to enhance adaptive immune responses. By contrast, strong stress induces even higher GC levels and causes chronic inflammation and autoimmunity. Because GCs can enhance the differentiation and function of T-helper 2 (Th 2) and Th 17 cells, high stress-induced GC levels might enhance inflammation via Th 17 cell differentiation. Overall, the positive and negative effects of GCs may regulate the balance between normal immune responses and susceptibility to infections and inflammatory diseases.